Formation of Greenhouse Gases in Woodchip Denitrification Treating Aquaculture Effluents : A Case Study - Lindholm-Lehto, Petra (Herald Scholarly Open Access, 2025)
Woodchip bioreactors are used to carry out nitrate removal of nutrient-rich aquaculture effluents via denitrification. In certain conditions, greenhouse gases (GHG)s nitrous oxide (N2O), methane (CH4), and carbon dioxide (CO2) may be formed which have high global warming potentials (N2O 265 298 times and CH4 28 times that of CO2). This study focused on monitoring the GHGs (N2O, CO2, and CH4) at the woodchip bioreactor, treating the recirculating water of a recirculating aquaculture system (RAS) rearing rainbow trout (Oncorhynchus mykiss) for one year. High nitrate removal (on average 18 g N m-3 d-1, up to 98%) were achieved. The highest rate of N2O removal (ranged from 0 to 45 μg m-2 h-1, 0 13.4 mg CO2-eq m-2 h-1), CO2 (10-450 mg m-2 h-1), and CH4 (from 0.1 to 2.5 mg m-2 h-1, 2.8-70 mg CO2-eq m-2 h-1) were observed in the warmer summer period, likely due to increased microbial actions.
Keywords: carbon dioxide; denitrification; farmed fish; nitrous oxide; woodchip bioreactor